Impact of RE-rich phases on magnetic properties in RE–Fe–B-sintered magnets by Tb diffusion - Qiang Li; Zhaohui Chen; He Chong; Hongyun Guo; Zhifeng Huang; Qing Zhou; Weibin Cui (Materials Research Letters)
We investigated the effect of Tb grain boundary diffusion on the structural transformation and magnetic properties across operational temperature ranges. Through micro-structural characterization, Fm[Formula: see text]m-type and Ia[Formula: see text]-type RE-rich phases were observed, and their effects on the magnetic properties were investigated. The distinct atomic distribution in the Ia[Formula: see text]-type phase characteristic [111] zone axis was observed via HAADF images in the diffused magnet. The Ia[Formula: see text]-type phase exhibited a lower lattice misfit with RE2Fe14B, favoring the formation of a larger nucleation field. The other grain boundaries with low coherence exhibit significant Cu enrichment. The lower lattice misfit and Cu-rich zone are critical for higher coercivity.